The role of the storyteller in old Norse literature - McMahon, B (2017)
This thesis examines the figure of the oral storyteller as depicted in various Old Norse literary sources written down during the High Middle Ages, the majority in Iceland, between the mid-twelfth and early fourteenth centuries. It comprises a literary-critical discussion of how storytellers and the art of storytelling are imagined, interpreted and represented within these texts. Where possible, connections are drawn between genres, and across considerable temporal and geographical distances, in order to illustrate the strength and endurance of cultural preoccupations with disguise, narrative structure and the role of intermediaries in different historical and creative contexts. The central contention is that the eddic poets and saga authors shared a common and profound sensitivity to the metatextual dimension of the storytelling endeavour in which they were engaged, and that this sensitivity manifested itself in strikingly similar ways across the whole period. The thesis is structured thematically, rather than chronologically, in order to foreground enduring cultural trends. The first chapter discusses the metatextual tendencies of the eddic poets, noting their recurring interest in disguise and the assertion (or appropriation) of an identity by characters who feature in their stories. It also includes an analysis of Vǫluspá which suggests that the poem lends itself to recitation by multiple performers. Chapter Two analyses depictions of public storytelling in the sagas and the relationship between writer and oral reciter as presented in the prologues and epilogues composed to ‘frame’ a number of these texts. Chapters Three and Four contain close readings of passages from the Sagas of Icelanders and eddic poetry, which demonstrate how certain characters, often of low social status, temporarily take on the mantle of a storyteller and perform their accounts of events so as to illuminate the texts' broader interest in the mechanics of literary narrative.